2021
DOI: 10.3389/fnins.2021.689629
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture Improves M2 Microglia Polarization and Glia Anti-inflammation of Hippocampus in Alzheimer’s Disease

Abstract: Background: Alzheimer’s disease (AD) is a neurodegenerative disease characterized by loss of recognition and memory. Neuroinflammation plays pivotal roles in the pathology of AD and affects the progression of the disease. Astrocyte and microglia, as main immune executors in the central nervous system (CNS), participate into the inflammatory response in AD. Glia polarize into different phenotypes during neurodegeneration. Pro-inflammatory glia produce cytokines (IL-1β, TNF-α, and IL-6) resulting into debris agg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 27 publications
3
46
0
1
Order By: Relevance
“…AD patients have a high expression of NADPH oxidase in microglia ( Choi et al, 2012 ), and inhibiting NADPH oxidase drives microglia phenotype from M1 to M2, which is a potential therapeutic approach in AD ( Choi et al, 2012 ). Electroacupuncture, a widely used Chinese traditional therapy, improved learning, and memory of AD rats, inhibited the activation of glia and polarized microglia toward M2 phenotype in hippocampus of AD rats with decreased pro-inflammatory cytokines and increased anti-inflammatory cytokines by inhibiting NF-κB pathway but activating STAT-6 pathway ( Xie et al, 2021 ). Over-expression of thymosin β4 (Tβ4), a constituent part of cytoplasm and cytoskeleton, improved neuronal function and cognitive ability, reduced brain Aβ accumulation, upregulated insulin-degrading enzyme, and alleviated neuroinflammatory response by converting microglia and astrocyte to neuroprotective phenotype in APP/PS1 mice via negative regulation of TLR4/MyD88/NF-κB p65 and p52 pathways ( Wang et al, 2021 ).…”
Section: Other Factors Inducing Microglia Polarization In Neurodegene...mentioning
confidence: 99%
“…AD patients have a high expression of NADPH oxidase in microglia ( Choi et al, 2012 ), and inhibiting NADPH oxidase drives microglia phenotype from M1 to M2, which is a potential therapeutic approach in AD ( Choi et al, 2012 ). Electroacupuncture, a widely used Chinese traditional therapy, improved learning, and memory of AD rats, inhibited the activation of glia and polarized microglia toward M2 phenotype in hippocampus of AD rats with decreased pro-inflammatory cytokines and increased anti-inflammatory cytokines by inhibiting NF-κB pathway but activating STAT-6 pathway ( Xie et al, 2021 ). Over-expression of thymosin β4 (Tβ4), a constituent part of cytoplasm and cytoskeleton, improved neuronal function and cognitive ability, reduced brain Aβ accumulation, upregulated insulin-degrading enzyme, and alleviated neuroinflammatory response by converting microglia and astrocyte to neuroprotective phenotype in APP/PS1 mice via negative regulation of TLR4/MyD88/NF-κB p65 and p52 pathways ( Wang et al, 2021 ).…”
Section: Other Factors Inducing Microglia Polarization In Neurodegene...mentioning
confidence: 99%
“…5 C). To further uncover whether circ_0012381 induces the M2 polarization of HMC3 cells by sponging with miR-340-5p, we checked the expression of the M2 marker ARG1 [ 28 , 29 ]. The result illustrated that circ_0012381 and miR-340-5p inhibitor significantly upregulated ARG1 expression (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Animal studies have contributed to the discovery of the mechanism by which electroacupuncture protects neurons in Alzheimer's disease. Recent investigations have demonstrated that electroacupuncture can control the microglia activation [ 39 ] and reduce the production of neuroinflammatory markers of brain [ 40 , 41 ]. However, the research above mostly focused on the hippocampus, with no evidence of electroacupuncture intervention on neuroinflammatory factors and microglia cell activation in other brain areas.…”
Section: Discussionmentioning
confidence: 99%